Gambaran Kemampuan Fitting Frame Pada Bagian Pad Arm Di Optik Daerah Kendari Tahun 2022 - Sari, Dian Leila (LPPM Universitas Dharma Andalas, 2022)
The importance of choosing a nosepad that fits the type of frame by the practitioner is one of the main factors in wearing comfort. The most adjustable parts of the frame are the handle and the nosepad, so a practitioner should choose an easy-to-adjust nosepad. In addition, it would be great if the selected frame has a distance between the nosepads that is not much different from the size of the bridge of the nose where the pad will be attached. This is to avoid changing the shape of the nosepad holder which is too extreme. The purpose of the research to be achieved by the author is to describe the ability of the Frame Fitting on the Pad Arm section of the Kendari area of optics. The type of research used in this research is qualitative research Based on the results of the research and discussion in the previous chapter, 5 informants who are considered to represent optics in the Kendari area, the results are obtained. standard splay angle, front angle, and vertical angle as well as the term pad arm. The standard fitting capability is always carried out by the 5 optics located in the kendari area. Practitioners who represent 5 opticians in the Kendari area always prioritize the comfort of their customers. They don't discriminate against any customer who needs their services. Practitioners use special tools to make fittings, especially on the eyeglass pad arm.